Imunidades relativas ás entidades beneficentes de assistência social - Ferreira, Alex Sandro Sarmento (2010)
Tax immunities operate as instruments for the protection of fundamental rights consituting rules for the protection of other rights. They represent real constitutional guarantees since they aim to buffer certain fundamental rights. Our aim is to promote an epistemological analysis of the tax immunity rules, in particular those that deal with social assistance charities. Initially, we will establish the premises that will be built upon in order that the reader may determine the normative mold used to set out the line of reasoning applied. We will therefore touch on the principles that are most strongly linked to tax immunity, the definition of taxation power and taxation competence. We will go back in history to the appearance of fiscal exoneration as well as studies of the diverse definitions of tax immunity. In consideration of the fact that tax immunities are fundamentally linked to the theory of values, we will investigate the strong connection between the rules of immunity and the values consecrated in our constitution. We will reflect on the dichotomist and trichotomist undercurrents and the normative mold that most tax immunity norms must be based on. Based on the premises set out we will begin in chapter VII the analysis of the generic immunities of article 150, paragraph VI of the Federal Constitution whilst considering the analysis of jurisprudence on this topic. In the following chapter we will focus on the immunities of social charity organizations and the requirements imposed by Law 12.101/09 in particular. We will make an analysis of the above mentioned law based on article 14 of the National Taxation Code as well as a detailed analysis of the constitutionality of these requirements